(untitled) (Asia Pacific Journal of Social Innovation, 2024)
Psychomotor performance among basic physical education students is a crucial aspect that needs to be addressed amidst COVID-19 pandemic. The disruptions, changes and consequences given by this pandemic had caused students’ mental or psychological state to be disturbed which in turn, affects psychomotor performance among basic physical education collegiate students. Amidst the pandemic, there is an increased interest on how mental health problems among collegiate students were being affected due to sudden changes in the perspective of clinical field, surgeons and athletes. What remains to be explored, however, is how students’ mental health was affected by this pandemic which in turn influence their psychomotor performance in the field of physical education. Moreover, the direct effect of mental health problem to psychomotor performance is yet to be explored. To address this gap, this study examined the relationship between mental health and students’ psychomotor performance. Quantitative approach, specifically correlational analysis, was used to analyze data from 500 respondents coming from one of the Universities of Mindanao Philippines who were enrolled in basic Physical Education subject. Bivariate regression analysis assessed the relationship between mental health and psychomotor performance. It was found that the unstandardized beta coefficients between mental health in terms of psychological distress, major depression and generalized anxiety and psychomotor performance with the p-value of 0.000, 0.000 and 0.002 respectively were statistically significant, which means that mental health problems had significant direct effect on psychomotor performance. Therefore, this study had found that mental h 1th problems directly influence psychomotor performance of basic physical education students.